Response of shallots growth and yield to phosphate fertilizer and Trichoderma application on peat soil. Issue 1 (February 2021) - Suparman,; Nugroho, W A
Abstract: Cultivating shallots on peat soils is quite challenging since it is considered less fertile regarding its high organic acid content and low nutrient availability. Trichoderma, as one of the plant-growth-promoting fungi (PGPF), is beneficial to promote shallots growth. However, there is still lack of information concerning its effectiveness and interaction effect with inorganic P fertilizer in peat soils. This study aimed to investigate the effect of Trichoderma application and P fertilization on the growth and yield of shallots on peat soils. A pot experiment arranged in a completely randomized design was conducted with two treatment factors. The first factor was P fertilizer comprised four application rates: 0, 100, 200, and 300 kg ha −1 . Meanwhile, as the second factor, Trichoderma treatment consisted of four application rates: 0, 2, 4, and 6 g plant −1 . The results showed an interaction effect of P treatment and Trichoderma on shallots growth and yield. A treatment combination of 2 g plant −1 Trichoderma without P fertilizer addition increased yield by 34% compared to control. This yield was relatively similar to 100 kg ha −1 P fertilizer without Trichoderma addition. It is proved that the Trichoderma application could reduce inorganic P fertilizer input.